Researches on cognitive sequelae of burn injury: Current status and advances - Xie, Chenchen; Hu, Jun; Cheng, Yong; Yao, Zhongxiang (Frontiers in Neuroscience, 2022)
Burn injury is a devastating disease with high rates of incidence, disability, and mortality, which can lead to neurological sequelae. The cognitive dysfunctions, such as memory defects, are the main neurological sequelae which are associated with the quality of life of burn injured patients. The post-burn cognitive dysfunctions are related to the primary peripheral factors and the secondary cerebral inflammation, which result in the destruction of blood-brain barrier (BBB). It showed a leakiness of BBB after burn injury by dual source CT and MRI techniques. As part of the neurovascular unit, BBB is vital to the nutrition and homeostasis of central nervous system (CNS) and undergoes myriad alterations after burn injury which correlates with the post-burn cognitive defects. Cognitive dysfunctions after burn injury are the critical part of sequelae which could not be ignored in the processes of diagnosis and treatment of burn injured patients. The main manifestation and intervention treatment of post-burn cognitive impairments are summarized. The mechanisms involved in memory defects, such as neuroinflammation, destruction of BBB, and hormone imbalances are also reviewed.